Compassionate use of medicinal Cannabis for pain treatment in children with Klippel-Trenaunay Syndrome. Case report - Michelle dos Santos Severino Costa; Caroline Carvalho Mageste; Flavio Henrique Esteves Guedes; Leticia Pontes Reis; Luisa Hermetrio Lazzarini; Ariel de Freitas Quintão Américo (BrJP)
BACKGROUND AND OBJECTIVES: Klippel-Trenaunay syndrome (KTS) is a rare congenital disease that manifests at birth or in childhood and has an unknown etiology, with no ethnic or gender predilection. Pain management, common in many cases, is challenging due to the complexity of the factors involved. The aim of this report is to demonstrate the effective use of a multimodal approach, including medicinal cannabis, in the treatment of pain in a child with KTS. CASE REPORT: this is the case of a child suffering from CTS who had severe chronic pain, significantly compromising his quality of life. The pain was managed with pharmacological therapies, including the use of medicinal cannabis as a therapeutic alternative when conventional treatments proved insufficient. The multimodal approach, which included the use of tetrahydrocannabinol, led to a reduction in pain and an improvement in the patient’s quality of life. Medical cannabis therapy proved to be an effective option, especially in cases of pain refractory to other interventions. CONCLUSION: The treatment of pain in patients with KTS should be multimodal, with an emphasis on non-invasive approaches. The use of medicinal cannabis is a viable and safe alternative, particularly in situations where conventional treatments do not provide adequate relief.